MORPHOLOGICAL ERRORS MADE BY THE THIRD SEMESTER STUDENTS OF THE ENGLISH DEPARTMENT OF STKIP PGRI SUMATERA BARAT IN WRITING ARGUMENTATIVE ESSAYS - Muhammad Khairi Ikhsan (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2019)
This article was written based on the students’ problems in writing argumentative essays. Those problems were mostly concerned with the morphological errors committed by the students in their writings. There were six points of morphological errors that the researcher focused on; incorrect third person singular verbs, incorrect past form, incorrect indifinite article, incorrect past participle, incorrect comparative and incorrect possessive case (Dulay, 1982). The purpose of this research was to describe the morphological errors committed by the students in writing argumentative essays. This research was conducted at English Education Department of STKIP PGRI Sumatera Barat. The research findings showed that the six types of morphological errors stated above were found by the researcher in the students’ writings. Thus, it could be concluded that the students had lack of comprehension on morphological study in writing argumentative essays.